Longitudinal associations between fathers' mental health and the quality of their coparenting relationships. (7th July 2015) - Price‐Robertson, Rhys; Baxter, Jennifer; Mathews, Stephanie
Abstract: Background: Although the body of research on fathers' mental health is growing, very few studies have explored the relationship between paternal mental health and coparenting. Coparenting is a construct that links different family subsystems, and refers to the ways in which parental figures relate to one another in their roles as parents. Methods: This study used data from 4, 933 families to explore the relationship between co‐resident fathers' mental health and the quality of their coparenting relationships, based on a limited set of coparenting items but utilising both fathers' and mothers' reports from three waves of the nationally representative L ongitudinal S tudy of A ustralian C hildren . Results: Results indicated an association between fathers' mental health and the quality of their coparenting relationships, after controlling for variables such as parental relationship happiness, father involvement, and maternal mental health. Fathers who reported mild or serious psychological distress were more likely to report lower quality coparenting relationships. Furthermore, fathers' and mothers' reports of the coparental relationship were broadly comparable, indicating that the association between fathers' mental health and coparenting quality could not be attributed entirely to the negative effect of mental distress on fathers' appraisals of their own coparenting. Conclusions: These findings suggest that it may be advantageous to develop clinical interventions that focus specifically on engendering coparenting skills in families where the father has mental health concerns. Abstract :